Pengaruh Content Marketing dan Influencer Marketing terhadap Keputusan Pembelian Otak-Otak Kabupaten Bintan - Lusiana Purba; Febi Rosaria; Restu Prasetyo Andriyatno (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to understand the influence of content marketing and influencer marketing on otak-otak purchasing decisions in Bintan Regency. The method used is a quantitative survey with online data collection via Google Form to 59 respondents aged 15-40 years who have consumed otak-otak in the area. Data were analyzed using SPSS software based on consumer behavior theory and the AIDA model, which focuses on how content and influencers can influence purchasing interest.The results of the study show that content marketing and influencer marketing significantly influence otak-otak purchasing decisions. Interesting content and trust in influencers can increase consumer interest and desire to buy the product. This finding shows the importance of the right digital marketing strategy in supporting local MSMEs to be able to compete and increase sales of regional products.However, this study has limitations in small samples and is limited to certain areas, so the results do not represent the entire population of otak-otak consumers in Bintan Regency. However, this study provides a practical contribution for MSME actors and local marketers to design more effective and targeted digital marketing strategies. Academically, this study enriches the study of digital marketing and consumer behavior in the local food industry.